Opportunities and Challenges of Industries 4.0 and 5.0 in Latin America - Germán D. Rueda-Carvajal; Oscar A. Tobar-Rosero; Gabriel J. Sánchez-Zuluaga; John E. Candelo-Becerra; Héctor Andrés Flórez-Celis (Sci)
The Fourth Industrial Revolution is transforming global industries. However, Latin America faces significant challenges in adopting these technologies. Particularly, small- and medium-sized enterprises constitute the backbone of the economy in the region. This study analyzes the technological gap between Latin America and more developed regions, focusing on public policies, infrastructure, and gap-closing training. Based on a systematic literature review and secondary data analysis, this research highlights key indicators such as digital infrastructure, investment in research and development, and the effectiveness of government strategies in promoting Industry 4.0 and Industry 5.0. Results reveal that Latin America lags behind Europe and Asia in applications related to Internet of Things, cloud infrastructure, and artificial intelligence. However, there are opportunities for improvement through targeted public policies, increased investment in research and development, and enhanced collaboration between the public and private sectors. The study concludes that bridging the digital divide requires a holistic approach that includes improving infrastructure, fostering digital skills, and creating favorable regulatory environments. This research stands out from similar studies by providing a detailed analysis of the regional barriers to adopting Industry 4.0 and Industry 5.0 and offering concrete recommendations for policymakers.